EVALUASI SIFAT PRODUKSI TELUR DAN BERAT TELUR AYAM LOKAL NUSA TENGGARA TIMUR - Arnold Ch. Tabun; Bernadus Ndoen; David Liunokas (Politeknik Pertanian Negeri Kupang, 2010)
Egg Production Character Evaluation And Heavy Local Chicken's Egg At East Nusa Tenggara. The experiment about genetic potential evaluation for the characteristics of egg production and egg weight of local chickens in East Nusa Tenggara has been conducted in animal production housing Animal husbandry department, Polytechnic of Agriculture Kupang. The objective of this study is determine the genetic potency of local chicken in terms of their egg production, heritability value of egg production characteristic and egg weight of local chicken in East Nusa Tenggara.Randomized complete block design was applied in this experiment by using Anova of heritability. The results show that the average of egg production of local chicken is 60,67% Â± 2.5, white the egg weight is 0,38 (38%) Â± 2,8. These findings show that local chicken has genetic potency for egg production which is above egg production average (60%) and egg weight is categorized as medium egg weight with (heritability value 0-1). The big standard deviation is probably due to the big variation of local chicken variety and their genetics that are needed to develop.In conclusion, local chicken in East Nusa Tenggara has genetic potency to be developed because of their heritability value of egg production which is above the egg production average and their egg weight is medium.Keywords: Local chicken, heretability value, egg production and egg weight